EFEKTIVITAS PENGGUNAAN APLIKASI Male_O 1.9 ( Studi di Kantor Regional XI Badan Kepegawaian Negara Manado Bidang Pengangkatan dan Pensiun ) - MELISA CAROLINE ILAT; WELSON ROMPAS; Rully Mambo (JURNAL ADMINISTRASI PUBLIK, 2023)
This research is to find out how effective the use of the Male_O 1.9 application is at the Regional Office XI of the Manado State Civil Service Agency for Appointment and Retirement? This research aims to determine the effectiveness of using the Male_O 1.9 application at the Regional Office XI of the Manado State Civil Service Agency in the field of appointment and retirement. This research is a qualitative research. The informants in this research were the creator of the Male_O 1.9 application, the head of the appointment and retirement sector, employees in the appointment and retirement sector, BKD employees, and civil servants. Collecting data using observation techniques, interviews, and retrieval of documentation. Data analysis in this study used data reduction, data presentation, and drawing conclusions. The results of the research show the effectiveness of using the Male_O 1.9 application, namely: (1) Achievement of objectives, the Male_O 1.9 application for service time is not good enough, the service time provided must be increased, as well as clarity on the targets of the Male_O 1.9 application, (2) Integration, The Male_O 1.9 application, seen from the procedures, already has clear procedures, but is still considered too complicated, because data input is not carried out directly by civil servants, and there is a lack of socialization from BKN employees to civil servants regarding returning files, (3) Adaptation, employees are able to adapt to the Male_O 1.9 application, seen from the increase in ability from those who don’t understand until they understand and understand how the Male_O 1.9 application works.